ANALISIS BUDAYA ORGANISASI DAN MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KINERJA GURU SMK BAKTI KENCANA CIMAHI - Fiqri Rianto; Juddy Prabowo (ITB AAS Indonesia Surakarta, 2025)
This research aims to determine the influence of organizational culture and work motivation variables, both simultaneously and partially, on teacher performance variables at SMK Bakti Kencana Cimahi. This research uses a quantitative approach to describe whether or not there is an influence of organizational culture variables (X1) and work motivation (X2) on teacher performance (Y). This research uses primary data through questionnaires distributed to 37 respondents. The respondents in this research were teachers at Bakti Kencana Cimahi Vocational School. This research uses quantitative descriptive and quantitative associative analysis methods using the coefficient of determination and multiple regression analysis. The data obtained was then processed using the SPSS 26.0 application. The results of the research show that the organizational culture at SMK Bakti Kencana Cimahi is included in the criteria Enough, with maximum criteria very strong. Work motivation is included in the criteria Enough with maximum criteria very high. Teacher performance is within the criteria Enough with maximum criteria Very good. The results of subsequent research show that organizational culture and work motivation simultaneously influence teacher performance variables. Apart from that, organizational culture has a positive influence on teacher performance, as well as work motivation.